Health Implications of Domestic Wastewater Treatment Through Biofilter Technology in Indonesia: A Review - Sari, Dilla Puspita; Defriani; Amelia, Hutri; Fadila, Rahma Resky (Journal of Epidemiology and Health Science, 2026)
Background: Domestic wastewater originates from household, industrial, and commercial activities, containing major pollutants such as BOD, COD, TSS, oil, fat, ammonia, and coliform which are dangerous if not treated according to the quality standards of the Minister of Environment and Forestry Regulation No. 68/2016. Biofilter technology (aerobic, anaerobic, or a combination) is a practical, economical, efficient solution, and suitable for limited land. Biofilters work with microbes attached to the media, effectively reducing the pollutant load, are easy to operate, and are superior to septic tanks. However, implementation still faces obstacles regarding material and construction standards. Objective: This study aims to review scientific articles related to the Health Implications of Domestic Wastewater Treatment Through Biofilter Technology. Methods: This article uses a narrative literature review to assess the health impacts of biofilter technology in domestic wastewater treatment. The literature was searched through SpringerLink, Scopus, and Google Scholar, focusing on publications from 2020–2025, using keywords related to biofilters, domestic wastewater, public health, sanitation, and water quality. Results: The results of this study indicate that the use of biofilter technology in managing liquid waste is relevant not only in the household sector, but also in healthcare institutions. Maintaining effluent quality according to established standards is crucial to avoid adverse effects on the environment and public health, such as increased cases of diarrhea or skin infections due to contaminated water. In addition, several studies highlight that water treated by biofilters can be reused, for example for watering open areas and gardens, thus providing additional benefits from the aspect of water resource sustainability. Conclusion: Based on studies from several journals, the issue of liquid waste generated from households and healthcare facilities is caused by a lack of public awareness and minimal management infrastructure. Major pollutants such as BOD, COD, TSS, oil, ammonia, and coliform have significant negative effects on the environment and public health. Biofilter technology has proven effective in reducing pollution loads to meet established standards, although there are several parameters that still require extra attention. Improved design, education, and regulatory support are essential to improve environmental quality and public health. Keywords: Domestic wastewater treatment, Biofilter, Environmental pollution, Sanitation, Public health.